Second ionization constant of sulfuric acid in H2O and D2O from 150 to 300 °C at p = 11.5 MPa using flow AC conductivity. Issue 3 (21st December 2022) - Conrad, Jacy K.; Arcis, Hugues; Ferguson, Jane P.; Tremaine, Peter R.
Abstract : The ionization constants of bisulfate in light and heavy water at high temperatures were determined from new AC conductivity measurements using a custom-built instrument and the Quint–Viallard conductivity model. Abstract : A custom-built flow-through AC conductivity instrument was used to measure the deuterium isotope effect on the ionization quotient of bisulfate from 150 to 300 °C, at p = 11.5 MPa. Standardized solutions of KCl, HCl, KOH, KHSO4, K2 SO4, and H2 SO4 were prepared in light and heavy waters and their conductivities were measured and fitted with the Quint–Viallard conductivity model to obtain single ion conductivities at infinite dilution for K +, Cl −, H +, OH −, HSO4 −, and SO4 2− . These are the first conductivities of DSO4 − and SO4 2− measured in heavy water at any temperature, and the first ionization constants for bisulfate reported in heavy water above 225 °C. The deuterium isotope effect on the chemical equilibrium constant, Δp K 2a = p K 2a, D − p K 2a, H, was found to increase with temperature, in contrast to the behaviour seen for other simple oxyacids.